Analisis Akar Masalah Keterlambatan Pengerjaan pada Proyek Konstruksi Politeknik Maritim Negeri Indonesia - Naufal Iman Adzhan; Ary Setyawan; Koosdaryani Soeryodarundio (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The construction industry in Indonesia is growing rapidly, playing a crucial role in the country's economic, political, and social development. However, alongside this rapid growth, issues such as project delays are inevitable. The construction project of the Indonesian Maritime Polytechnic, for instance, has experienced significant delays, which can lead to increased costs, waste of human resources, and disputes among the involved parties. Understanding the primary causes of these delays is essential for developing effective strategies to avoid future delays. This analysis uses both qualitative and quantitative methods to identify the root causes of delays. Data was collected through surveys of respondents involved in the project, including project managers, field staff, and consultants. The analyzed causes of delays include insufficient funding, increases in raw material costs, additional costs, contract document errors, poor communication, and slow decision-making. To minimize delays and their impacts, several recommendations can be made: effective strategic planning, improved communication, increased staff, accurate initial cost estimates, and good management. By implementing these recommendations, the Indonesian Maritime Polytechnic construction project can be completed more effectively and efficiently, and future delays can be avoided.